TECHNOLOGY VALUE ENGINEERING AND ITS ROLE IN REDUCING COSTS AND IMPLEMENT LEADERSHIP STRATEGIC (AN APPLIED STUDY) (World Economics and Finance Bulletin, 2023)
In modern manufacturing environment the economic units are suffering from in the current situation due to the invasion of the market with various competing products at low prices, functional performance, and high quality compared to local products, which has placed the Iraqi economic units under a lot of pressures for various reasons, including an increase in the cost of their products and a decrease in the functional merit of their products. Because of its reliance on traditional approaches to cost management, the research therefore focused on applying the value engineering technique and its role in reducing costs and improving the value of the product in the men’s clothing factory in Najaf, in order to overcome the difficulties that the factory suffers from in order to reduce costs and improve the value of the product.